SAA drives proinflammatory heterotypic macrophage differentiation in the lung via CSF‐1R‐dependent signaling. Issue 9 (20th May 2014) - Anthony, Desiree; McQualter, Jonathan L.; Bishara, Maria; Lim, Ee X.; Yatmaz, Selcuk; Seow, Huei Jiunn; Hansen, Michelle; Thompson, Michelle; Hamilton, John A.; Irving, Louis B.; Levy, Bruce D.; Vlahos, Ross; et al.
Abstract : Serum amyloid A (SAA) is expressed locally in chronic inflammatory conditions such as chronic obstructive pulmonary disease (COPD), where macrophages that do not accord with the classic M1/M2 paradigm also accumulate. In this study, the role of SAA in regulating macrophage differentiation was investigated in vitro using human blood monocytes from healthy subjects and patients with COPD and in vivo using an airway SAA challenge model in BALB/c mice. Differentiation of human monocytes with SAA stimulated the proinflammatory monokines IL‐6 and IL‐1β concurrently with the M2 markers CD163 and IL‐10. Furthermore, SAA‐differentiated macrophages stimulated with lipopolysaccharide (LPS) expressed markedly higher levels of IL‐6 and IL1‐β. The ALX/FPR2 antagonist WRW4 reduced IL‐6 and IL‐1β expression but did not significantly inhibit phagocytic and efferocytic activity. In vivo, SAA administration induced the development of a CD11c high CD11b high macrophage population that generated higher levels of IL6, IL‐1β, and G‐CSF following ex vivo LPS challenge. Blocking CSF‐1R signaling effectively reduced the number of CD11c high CD11b high macrophages by 71% and also markedly inhibited neutrophilic inflammation by 80%. In conclusion, our findings suggest that SAA can promote a distinct CD11c high CD11b high macrophage phenotype, and targeting this population may provide a novel approach to treating chronic inflammatory conditions associated with persistent SAA expression.—Anthony, D., McQualter, J. L., Bishara, M., Lim, E. X., Yatmaz, S., Seow, H. J., Hansen, M., Thompson, M., Hamilton, J. A., Irving, L. B., Levy, B. D., Vlahos, R., Anderson, G. P., Bozinovski, S. SAA drives proinflammatory heterotypic macrophage differentiation in the lung via CSF‐1R‐dependent signaling. FASEB J. 28, 3867‐3877 (2014). www.fasebj.org